2020
DOI: 10.21101/cejph.a6126
|View full text |Cite
|
Sign up to set email alerts
|

Identifying risk factors of severe early childhood caries in infants from Bosnia and Herzegovina

Abstract: Objective: The aim of the study was to investigate risk factors for S-ECC among infants under 24 months of age living in Banja Luka, Bosnia and Herzegovina.Methods: A cross-sectional population-based study was carried out. Considering inclusion criteria, the total sample consisted of 192 examined infants under 24 months of age. Parents/caregivers were interviewed ahead of each dental examination of children. Following data collection, outcome measures were: the presence/absence of S-ECC (children with at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Though the impact of frequency and duration of breastfeeding during day and night time on ECC was assessed cross-sectionally by Chanpum et al 41 and Dissanayaka and Gamage, 83 only the breastfeeding to sleep and oral cleaning practices after breastfeeding were significantly associated with ECC prevalence and caries experience. Obradović et al 47 authenticated the above finding indicating that breastfeeding or bottle-feeding at night was significantly associated with S-ECC among children aged birth to 24 months. As investigated by Peres et al, 31 children breastfed ≥24 months had a 2.4 times higher risk of S-ECC than children breastfed for <12 months.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Though the impact of frequency and duration of breastfeeding during day and night time on ECC was assessed cross-sectionally by Chanpum et al 41 and Dissanayaka and Gamage, 83 only the breastfeeding to sleep and oral cleaning practices after breastfeeding were significantly associated with ECC prevalence and caries experience. Obradović et al 47 authenticated the above finding indicating that breastfeeding or bottle-feeding at night was significantly associated with S-ECC among children aged birth to 24 months. As investigated by Peres et al, 31 children breastfed ≥24 months had a 2.4 times higher risk of S-ECC than children breastfed for <12 months.…”
Section: Resultsmentioning
confidence: 82%
“…Sugar consumption was found to be correlated with the ECC burden in the EU member states after analyzing the systematic data obtained from the Food and Agriculture Organization of the United Nations. 7 Obradović et al 47 and Olczak-Kowalczyk et al 48 also observed a strong correlation between the occurrence of ECC and prominent risk factors such as consumption of sweetened food within the first 2 years of age (odds ratio [OR] = 2.96) and nocturnal drinking of sweet beverages by the over-12-month-old child (OR = 1.95). However, all these studies are cross-sectional studies that are quite unable to determine the independent and actual effect of the particular phenomenon.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…If they had not done it on the very start (infant period), they should have to be obliged to perform it in crucial toddler period. Although it was previously considered as late, preschool period can still offer important ways for intervention in established ECC processes, if the disease has already not been prevented ( 1 - 3 , 32 ). This should be the way to create reasonable circumstances not to intervene later in dental caries process of (young) permanent teeth in children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dental disease prevention in Bosnia and Herzegovina is poor, there is no national prevention plan or protocols that is consistently implemented. High caries prevalence among our children, especially those of low socio-economic status or lack of access to dental care, is an indicator [20,21]. Unfortunately, with a reduction in the provision of preventive measures, COVID-19 worsened an already unfavourable situation.…”
Section: Discussionmentioning
confidence: 99%